Menguak Nilai-Nilai Demokrasi dalam Islam - Masruhan Masruhan (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2008)
Democracy is a political concept about which all people discuss nowadays. It has become integral and inseparable part of modern life. All people from many countries proclaim that their countries are democratic. Though, Hamid Enayat has asserted that no form of government can be called democratic with our current understanding without fulfillment of several principles and clear stipulation in its constitution. A couple essential principles is acknowledgment of human rights, rule of law, equality before the law of all citizens regardless of their tribes, races, and ethnic groups, likelihood of state decisions with the popular consent, and high level tolerance towards unconventional and unorthodox views.On the other hand, some modern writers have proclaimed that the concept of political Islam is democratic. This article discovers democratic values available in Islamic teaching. Is it true that Islamic teaching contains those values? Are there fundamental differences between modern democratic values with those in Islamic teaching and those practiced throughout Islamic history? Such questions should be put forward to avoid misunderstanding and clash between Islam and democracy. It is that basis that this article wishes to observe the concept of political Islam from the perspective of principles on which unit of socio-political is founded and at the same time locate merging points between the application of Islamic shura principles and the main aim of a democratic government.